LDL-mimetic lipid nanoparticles prepared by surface KAT ligation for in vivo MRI of atherosclerosis. Issue 44 (19th October 2020) - Fracassi, Alessandro; Cao, Jianbo; Yoshizawa-Sugata, Naoko; Tóth, Éva; Archer, Corey; Gröninger, Olivier; Ricciotti, Emanuela; Tang, Soon Yew; Handschin, Stephan; Bourgeois, Jean-Pascal; Ray, Ankita; Liosi, Korinne; et al.
Abstract : LDL-mimetic lipid nanoparticles, decorated with MRI contrast agents and fluorescent dyes, were prepared by the covalent attachments of an apoB100-mimetic peptide, Gd(iii )-chelate, and rhodamine to enhance atherosclerosis in the in vivo imaging. Abstract : Low-density lipoprotein (LDL)-mimetic lipid nanoparticles (LNPs), decorated with MRI contrast agents and fluorescent dyes, were prepared by the covalent attachment of apolipoprotein-mimetic peptide (P ), Gd(iii )-chelate (Gd ), and sulforhodamine B (R ) moieties on the LNP surface. The functionalized LNPs were prepared using the amide-forming potassium acyltrifluoroborate (KAT) ligation reaction. The KAT groups on the surface of LNPs were allowed to react with the corresponding hydroxylamine (HA) derivatives of P and Gd to provide bi-functionalized LNPs (PGd-LNP ). The reaction proceeded with excellent yields, as observed by ICP-MS (for B and Gd amounts) and MALDI-TOF-MS data, and did not alter the morphology of the LNPs (mean diameter: ca. 50 nm), as shown by DLS and cryoTEM analyses. With the help of the efficient KAT ligation, a high payload of Gd(iii )-chelate on the PGd-LNP surface ( ca. 2800 Gd atoms per LNP) was successfully achieved and provided a high r 1 relaxivity ( r 1 = 22.0 s −1 mM −1 at 1.4 T/60 MHz and 25 °C; r 1 = 8.2 s −1 mM −1 at 9.4 T/400 MHz and 37 °C). This bi-functionalized PGd-LNP was administered to three atherosclerotic apoE −/− mice to reveal the clear enhancement of atherosclerotic plaques in the brachiocephalic artery (BA) by MRI, in good agreement with the high accumulation of Gd in the aortic arch as shown by ICP-MS. The parallel in vivo MRI and ex vivo studies of whole mouse cryo-imaging were performed using triply functionalized LNPs with P, Gd, and R (PGdR-LNP ). The clear presence of atherosclerotic plaques in BA was observed by ex vivo bright field cryo-imaging, and they were also observed by high emission fluorescent imaging. These directly corresponded to the enhanced tissue in the in vivo MRI of the identical mouse.